Decision Making Method for KT Kopi Café Location Selection Using Analytical Hierarchy Process Method - Sylvia, Sylvia (Journal of Industrial Engineering & Management Research, 2022)
Decision Making in business location will have significant impact to long term profitability, survival and competitiveness of business. As important as it is, decision making also is challenging task as there will be criteria and alternatives complexity. This research will discuss about the application and implementation of Analytical Hierarchy Process Method in decision making for KT Kopi café location selection that currently located at North Sumatera. Currently the café location selection decision making is purely based on intuitive from management. In this research, the analysis and method used for decision making is Pairwise Comparison and Analytical Hierarchy process. The purpose is to recommend to KT Kopi of the methodological decision making process that based on criteria importance and weight. This decision making method will ensure that important criteria will be included and calculated in the decision making process. The research method using observation, literature study and interview with management to list the criteria that will contribute to the good café location selection decision making. Management is asked to give score of importance among three potential location based on eight criteria using pairwise comparison and afterward follows by the calculation of consistency ratio and calculation of rank using AHP. The result of the research shows that among three potential location A, B, and C, the location score using AHP and pairwise comparison for location A is 0.2673, location B is 0.3157 and location C is 0.4170. Therefore, based on each location’s score with eight criteria (market proximity, customers access convenience, raw material suppliers’ proximity, competition level, cost, labour potential, infrastructure & facilities), location C is the most preferred, following by location B then location A is the least preferred. The consistency ratio (CI/RI) value is 0.0337, which is less than 0.1, means the pairwise comparison data is consistent and can be used in AHP decision making analysis.